2005
DOI: 10.1016/j.cemconres.2004.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of capillary pore size characteristics in high-strength concrete at early ages

Abstract: Abstract:The quantitative SEM-BSE image analysis was used to evaluate capillary porosity and pore size distributions in high strength concretes at early ages. The Powers model for hydration of cement was applied to the interpretation of the results of image analysis. The image analysis revealed that pore size distributions in concretes with an extremely low water/binder ratio of 0.25 at early ages were discontinuous in the range of finer capillary pores. However, silica fume-containing concretes with a water/b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(32 citation statements)
references
References 11 publications
(10 reference statements)
0
30
1
Order By: Relevance
“…Table 3 shows that the porosities of concretes containing limestone powder and silica fume are slightly higher than the plain concretes of the same w/p. Previous studies have shown that the addition of up to 9% by mass of silica fume as a cement replacement material results in a significant reduction in the pore sizes and connectivities of the cement pastes or concretes [19,26]. If their /b values have to be similar, then the pore connectivities (b) of the concretes containing limestone powder and silica fume should be lower than those of plain concretes.…”
Section: A Pore Structure Parameter From Electrical Property Measuremmentioning
confidence: 95%
“…Table 3 shows that the porosities of concretes containing limestone powder and silica fume are slightly higher than the plain concretes of the same w/p. Previous studies have shown that the addition of up to 9% by mass of silica fume as a cement replacement material results in a significant reduction in the pore sizes and connectivities of the cement pastes or concretes [19,26]. If their /b values have to be similar, then the pore connectivities (b) of the concretes containing limestone powder and silica fume should be lower than those of plain concretes.…”
Section: A Pore Structure Parameter From Electrical Property Measuremmentioning
confidence: 95%
“…Principally, evaluation of various concrete properties, as well as effect of external interferences like loading, fire, etc. on the microstructure of concrete can be investigated using these methodologies [6][7][8][9][10][11][12][13][14].…”
Section: The Image Analysismentioning
confidence: 99%
“…The backscattered electron (BSE) image analysis technique could be used to evaluate the coarse pore system of cementicious materials [11,12] . Most importantly, the volume fraction of unhydrated cement in concrete and the characteristics of ITZ between aggregate and paste matrix can be quantitatively measured by the only SEM-BSE image analysis [13] .…”
Section: Introductionmentioning
confidence: 99%